ArchiMed: A Data Management System for Clinical Research in Imaging - Micard, Emilien; Husson, Damien; , CIC-IT Team; Felblinger, Jacques (Frontiers in ICT, 2016)
Context: There is a great need in clinical research with imaging to collect, to store, to organize and to process large amount of varied data according to legal requirements and research obligations. In practice, many laboratories or clinical research centers working in imaging domain have to manage innumerous images and their associated data without having sufficient IT (Information Technology) skills and resources to develop and to maintain a robust software solution. Since conventional infrastructure and data storage systems for medical image such as “Picture Archiving and Communication System” (PACS) may not be compatible with research needs, we propose a solution: ArchiMed, a complete storage and visualization solution developed for clinical research. Material and methods: ArchiMed is a service oriented server application written in Java EETM which is integrated into local clinical environments (imaging devices, post-processing workstations, others devices...) and allows to safely collect data from other collaborative centers. It ensures all kinds of imaging data storage with a “study centered” approach, quality control and interfacing with mainstream image analysis research tools. Results: With more than 10 millions of archived files for about 4TB stored with 116 studies, ArchiMed, in function for 5 years at CIC-IT of Nancy-France, is used every day by about 60 persons, among whom are engineers, researchers, clinicians and clinical trial project managers.